Xenotopic expression of alternative electron transport enzymes in animal mitochondria and their impact in health and disease. (23rd February 2018) - Camargo, André F.; Chioda, Marina M.; Rodrigues, Ana P. C.; Garcia, Geovana S.; McKinney, Emily A.; Jacobs, Howard T.; Oliveira, Marcos T.
Abstract: The mitochondrial respiratory chain in vertebrates and arthropods is different from that of most other eukaryotes because they lack alternative enzymes that provide electron transfer pathways additional to the oxidative phosphorylation (OXPHOS) system. However, the use of diverse experimental models, such as human cells in culture, Drosophila melanogaster and the mouse, has demonstrated that the transgenic expression of these alternative enzymes can impact positively many phenotypes associated with human mitochondrial and other cellular dysfunction, including those typically presented in complex IV deficiencies, Parkinson's, and Alzheimer's. In addition, these enzymes have recently provided extremely valuable data on how, when, and where reactive oxygen species, considered by many as "by‐products" of OXPHOS, can contribute to animal longevity. It has also been shown that the expression of the alternative enzymes is thermogenic in cultured cells, causes reproductive defects in flies, and enhances the deleterious phenotype of some mitochondrial disease models. Therefore, all the reported beneficial effects must be considered with caution, as these enzymes have been proposed to be deployed in putative gene therapies to treat human diseases. Here, we present a brief review of the scientific data accumulated over the past decade that show the benefits and the risks of introducing alternative branches of the electron transport into mammalian and insect mitochondria, and we provide a perspective on the future of this research field.